What I found out about her : stories of dreaming Americans - LaSalle, Peter (Richard Sullivan prize in short fiction., 2014)
Explores how everyday life for many--an FBI agent, a study-abroad student, a drug dealer's chic girlfriend, a trio of Broadway playwrights, among others--can almost take on the texture of a haunting dream.